Alternative energy source for heating system of woodworking enterprise - Савченко, Олена; Желих, Василь; Юркевич, Юрій; Козак, Христина; Багмет, Сергій; Savchenko, Olena; Zhelykh, Vasyl; Yurkevych, Yurii; Kozak, Khrystyna; Bahmet, Serhii (Lviv Politechnic Publishing House, 2018)
На деревообробних підприємствах наявна велика кількість відходів деревини, енергетичний потенціал яких можна використовувати як альтернативне джерело енергії для вироблення теплової енергії на котельнях. Одним з найдешевших та екологічно безпечних способів переробки органічних відходів деревини вважається газифікація. У процесі газифікації утворюється горючий газ, який доцільно використовувати для заощадження традиційних джерел енергії під час вироблення теплової енергії. Розглянуто конструкцію газогенераторної установки, яка призначена для утилізації відходів деревини та одночасного вироблення генераторного газу. Утворений генераторний газ використовується в опалювальній котельні деревообробного підприємства як альтернативне джерело енергії для приготування теплоносія системи опалення. Встановлено нижчу теплоту спалювання виробленого генераторного газу.

At woodworking enterprises, there is a large amount of wood waste the energy potential of which can be used as an alternative source of energy for the generation of heat energy at boiler houses. Gasification is one of the cheapest and environmentally friendly methods for processing organic wood waste and obtaining an additional source of energy. The process of gasification occurs when wood waste is heated to high temperatures in the presence of oxygen, which results in the generation of combustible gas. Producer gas should be used to save traditional energy sources in the generation of heat energy. This article discusses the design of the gasifier which is intended for utilization of wood waste from a wood-processing enterprise and the simultaneous generation of producer gas. Generted producer gas is used in a boiler-house of a wood-processing enterprise as an alternative source of energy for the preparation of the heating system coolant. The lower heat of generated producer gas combustion is established.
Альтернативне джерело енергії для системи опалення деревообробного підприємства
Keywords: відходи деревини; газогенератор; генераторний газ; теплота спалювання; waste wood; gasifier; producer gas; heat of combustion